Contested Meanings in the Egyptian Revolution - Sarah Anne Rennick (Socio, 2013)
The Egyptian revolution was carried out under a banner notable for its distinct lack of divisive sectarian or political ideology. Yet, two years later, the post-revolutionary scene looks strikingly different: the country is profoundly polarized and the political vision of what Egypt should become is hotly contested. A common narrative is the so-called hijacking of the revolution by Islamists; however, this implies that the revolution has one defined meaning whose parameters are recognized by all. I argue against this. Using Dobry’s (1983) concept of multisectorial mobilization, the article dissects the myth of a unified mass movement and argues instead in favor of “dispersed mobilization”. The differences in interpretation of the revolution’s slogans are set out, revealing the ideational contestation in demands and goals and how these are translated into specific political battles. In this sense, the revolution should not be conceived as merely the 18 days of anti-Mubarak protest but rather a continuous process still underway.